The association of FAT1 mutations with therapeutic outcomes in AML, especially in receiving venetoclax combination - Wang, Tao; Huang, Junxia; Jia, Yongqian; Li, Junting; Mou, Weiwei; Lu, Guang (Frontiers in Oncology, 2025)
ObjectiveThe role of FAT1 mutations in acute myeloid leukemia (AML) remains unclear, particularly regarding their impact on the chemosensitivity of AML patients. To elucidate the effect of FAT1 mutations on the therapeutic outcomes and prognosis of AML patients, we conducted this study.MethodsTo analyze the impact of FAT1 mutations, we obtained data from the LAML-KR cohort of the International Cancer Genome Consortium (ICGC), consisting of 205 patients. Additionally, we retrospectively collected data from 108 primary AML patients who received initial induction chemotherapy with a venetoclax combination regimen between January 2019 and December 2023 at Qingdao Medical College Affiliated Hospital and Shengli Oilfield Central Hospital (referred to as the Venetoclax-AML cohort). We analyzed the characteristics, clinical features, and molecular genetic features of FAT1 mutations, and assessed the impact of FAT1 mutations on therapeutic outcomes and prognosis in both cohorts.ResultsIn the public LAML-KR cohort (n = 205), the mutation rate of the FAT1 gene was approximately 15% (31/205), with a nonsynonymous mutation rate of about 6%. Patients with FAT1 mutations (including synonymous mutations) exhibited a higher tumor mutation burden (TMB) compared to wild-type patients (p < 0.001). Further analysis of the 83 patients in the LAML-KR cohort with complete clinical data showed that the mutation rates of P53, DNMT3A, FLT3, and NPM1 genes (including synonymous mutations) were higher in the FAT1 mutant group than in the wild-type group (p < 0.05). In our retrospective Venetoclax-AML cohort (n = 108), the nonsynonymous mutation rate of the FAT1 gene was approximately 13% (14/108), which was higher than the mutation rate in the public LAML-KR cohort. Moreover, only the P53 mutation rate was higher in FAT1 mutant patients (p < 0.01), while the mutation rates of DNMT3A, FLT3, and NPM1 genes showed no significant difference between FAT1 mutant and wild-type patients (p > 0.05). In both the LAML-KR and Venetoclax-AML cohorts, FAT1 mutant patients showed better initial induction chemotherapy outcomes compared to wild-type patients. However, in the LAML-KR cohort, there was no improvement in overall survival (OS) for FAT1 mutant patients (median survival time: 34.6 months vs. 41.7 months, p = 0.6757), whereas there was a trend toward improved progression-free survival (PFS) in the Venetoclax-AML cohort (p = 0.103).Interestingly, further analysis of P53 mutant patients (n = 17) in the Venetoclax-AML cohort revealed that FAT1 mutant patients had better initial induction chemotherapy outcomes and a trend toward improved PFS compared to wild-type patients (p = 0.1381).ConclusionAML patients with FAT1 mutations have better initial induction chemotherapy efficacy with venetoclax-based regimens compared to wild-type patients, and there is a trend toward improved PFS. This may be related to the improved efficacy and prognosis in P53 mutation-positive patients.